Investigating on the Residue of Organophosphate Pesticides in the Water of the Hablehrood River, Garmsar, Iran - Mohammad Safari; Ali Ahmadfazeli; Hassan Vatandoost; Mostafa Karimaee; Davood Panahi; Mohammadali Shokri; Mehdi Moradian; Zahra Soleimani (Tehran University of Medical Sciences, 2020)
Background: Organophosphate pesticides are of concern to the drinking water supply and high risks on human health. Methods: An occurrence survey was performed in the spring and summer of 2016 for 6 months to assess the prevalence of organophosphate pesticides in the Hablehrood River that is located in Semnan Province. Besides, 10 kinds of organophosphate pesticides were sampled in 5 stations. Moreover, were measured by Gas Chromatography (GC) was supported by an electron capture detector (ECD) and Turbochrom software. In all stations, Diazinon was detected in the spring and summer, but Malathion only in the spring. Results: The highest concentration of Diazinon was observed at the Mahmoud Abad station in spring (0.94ppb) and the Bonekooh station in the summer (0.93ppb). The highest and lowest concentrations of Malathion were detected in Mahmoud Abad (0.35ppb), and Gache station, respectively. Conclusion: The concentration of pesticides in BoneKooh and Mahmood Abad was higher than the standard.